Cost-Benefit Analysis of a Hybrid Biophysical Approach to Wave Energy Extraction: Bio-Oscillator - Hildebrand, Tabea; Fischer, Christian; Relano, Veronica; Gorman, Richard; Stevens, Craig (Frontiers in Marine Science, 2021)
A cost-benefit analysis is described for a novel wave energy converter design based on a marine hybrid biostructure – a combination of macroalgae, shellfish or other species on a built frame. The Bio-Oscillator design utilises a hard “skeleton” (e.g., carbon fibre, wood) on which biological organisms (e.g. shellfish, large macroalgae) are grown. As waves pass by, the load generated by the oscillating drag and inertia is transferred through mooring lines to power takeoff technology. This novel approach essentially reverses the typical marine engineering view that “bio-fouling is bad” and instead leverages off the added-drag of biological growth on structures. The approach results in a structure that is largely biodegradable, naturally self-replicating and synergistic with the background environment, self-de-risking in terms of failure impact and can leverage off its own form to enhance energy capture beyond a conventional design. This reduces impact while connecting with conventional marine industries such as aquaculture. A cost-benefit analysis examines the economic pros and cons of this approach, focusing on installation and material costs, along with benefits from synergistic production. The analysis suggests that in addition to typical wave energy obstacles (e.g. cable length, capture width and power take off) the benefits (biodegradability, harvestability, carbon reduction) of replacing much of the mass of the structure with living biological material can be included.